Реліктові типи намогильних знаків з Середньої Наддніпрянщини - Товкайло, М. (Народна творчість та етнографія, 2006)
This article is dedicated to the problems of characterization of the relic types ol the wooden columnlike tomb signs from Middle Naddniprianshchina. More than 700 of such memorials were found and explored by the author at 30 cemeteries in 23 towns in the valley of the left bank of the Dnipro during 1998-1999 and 2003-2004. They form a narrow line along the Dnipro for about 160 kin. Three main groups of the monuments are distinguished among them, each bearing the reminders of the Christian and Soviet ideologies. However, the level of influence and their manifestations for different groups ol tomb monuments weren't the same. They keep the symbols of pre-Christian age as well, such as spheres, circles, squares, rectangles, rhombs and the columnlike form of the monuments themselves.